Language in the Digital Era. Challenges and Perspectives. - Dejica, Daniel (De Gruyter, 2016)
Pinpointing the impact of new technologies on language and communication, this book highlights the evolution and changes undergone by humanities in conjunction with technological innovation and looks at how language has adapted to the challenges of today's digitised world.